Reducing food loss and waste: Five challenges for policy and research. (January 2021) - Cattaneo, Andrea; Sánchez, Marco V.; Torero, Máximo; Vos, Rob
Highlights: Economic decisions underlie much of food loss and waste (FLW) along supply chains. FLW measurement needs to improve and should account for both quantity and quality losses. FLW reduction should balance efficiency, food security and environmental objectives. More policy research needed to understand the trade-offs between these three goals. Available evidence and knowledge gaps point to five major policy challenges to reduce FLW. Abstract: Despite broad agreement in policy circles on the need to reduce food loss and waste (FLW), considerable gaps in information still exist. This paper identifies policy-relevant information gaps, summarizes recent research that tries to fill these gaps and identifies five challenges for researchers, policymakers and practitioners in reducing FLW. The five challenges identified are: (i) measuring and monitoring FLW, (ii) assessing benefits and costs of FLW reduction and the tradeoffs involved, (iii) designing FLW-related policies and interventions under limited information, (iv) understanding how interactions between stages along food value chain and across countries affect outcomes of FLW reduction efforts, (v) preparing for income transitions and the shifting relative importance of losses and waste as economies develop.